O papel do psicólogo comunitário na perspectiva dos membros de uma comunidade e de profissionais da assistência social - Viecheneski, Juliana Cristina (2014)
Ahead to new fields that have been opened for the performance of Psychology and the potential cross-presenting the face of social practices, is irrevocable consider the opportunity to bridge the knowledge of this science to diverse segments. Thus, it’s essential to consider the community framework. Several studies addressing similar themes, however, do not always take into consideration the opinion and perception of the community. Under this weighting, this article brings the analysis of people’s report from the community, participants in a community project called “SOU EU”, that was elaborated and conducted by the psychologist author of this article and Social Assistants connected to SUAS, about the role of the psychologists in the community. The research aimed to understand in what way this people notice the practices of a psychologist outside the clinical space, articulating actions in the/ with and to the community, as well as, repossess possible outcomes or failures in this practice and the reach of the comprehension that they provide. To enable this study took part 08 people from the community, participants from the “SOU EU” project and 02 professionals from the Social Assistance. For this analysis, interviews were conducted with the aim of collecting data about this perception. The data analysis was treated by analyzing the contents, having defined the categories from the speech of informants. The report enabled the participants to reflect on the role of the psychologist has constituted upon the community, besides presenting a parallel between the theoretical knowledge / scientific and practical / experienced. Also provides reflections on professional practice through the technical aspects of the profession and the difficulties encountered in this line of action while professional identity. There is also a need for more research favoring space and the popular expression, in view of the need to clarify the perception of the role of the community psychologist who, in practice, is still obscure and confused in the eyes of community.